Pengaruh Budaya Organisasi, Komitmen Organisasi, dan Lingkungan Kerja terhadap Kinerja Pegawai Direktorat Perbenihan Tanaman Pangan Jakarta pada Masa Pandemi Covid-19 - Aisyah Ismawati; Zackharia Rialmi (Politeknik Ganesha Medan, 2022)
This research uses quantitative methods to define the impact of organizational culture, organizational commitment, and work environment on employee performance. This research was performed using objects in the form of an employee of the Jakarta Food Crop Germination Directorate. The research became held using a saturated sample, specifically via taking the entire population of employees as many as 58 employees. The data collected in the study by using a questionnaire with google form on 58 employees. The analysis performed as part of the writing of this research was performed using the SmartPls 3.0 application. The conclusion that may be visible from the research method that has been accomplished are: 1) organizational culture has a good impact on worker performance. 2) organizational commitment has a huge impact on worker performance. 3) the work environment has a huge impact on employee performance. 4) organizational culture, organizational commitment, and work environment concurrently affect employee performance.